Adaptive reduction of the control effort in chattering-free sliding-mode control of uncertain nonlinear systems - Bartolini, Giorgio; Ferrara, Antonella; Pisano, Alessandro; Usai, Elio (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, Utkin's concept of equivalent control is extended to second-order sliding modes and a method to evaluate their estimate by means of a proper high bandwidth filter is discussed. The knowledge of the estimate of the equivalent control is the basis of an adaptation mechanism which is able to modulate the amplitude of the discontinuous control so that a reduction in the boundary layer and in the corresponding oscillations of the plant input is attained. The proposed adaptive procedure is applied to a simple mechanical system as an example.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka